Evaluation Of Cash Receipts And Expenditure Accounting Information Systems To Improve Internal Control - Maulana, Firman; Permatasari, Ditya (Gorontalo Accounting Journal, 2024)
This study aims to evaluate the information system, particularly in cash receipts and disbursements, at Metro Swalayan in Malang City. This research is qualitative with a descriptive approach, meaning it will examine and describe the phenomena being studied, whether social phenomena or those derived from individual or group thoughts. The results of this study indicate that the accounting information system for cash receipts and disbursements at Metro Swalayan is not yet in accordance with Mulyadi's theory and previous research. This discrepancy is due to adjustments to operational needs. The shipping and sales functions are combined with the cash receipts function for efficiency.